Is functional training functional? a systematic review of its effects in community-dwelling older adults - Chiung-ju Liu; Wen-Pin Chang; Yun Chan Shin; Yi-Ling Hu; Jane Morgan-Daniel (European Review of Aging and Physical Activity)
Abstract Background Age-related decline in physical and cognitive capacity increases older adults’ risk of disability, long-term care placement, and mortality rate. Functional training, which uses activities of daily living or simulated movements to complete activities as the intervention medium, could be more effective than rote exercise, which uses repetitive movements without added purpose, in preventing late-life disability in older people. With a growing number of studies in this area, systematically studying the effect of functional training is needed. The purpose of this systematic review was to examine the effects of functional training on the outcomes of activities of daily living, physical functioning, and cognitive function in community-dwelling older adults. Methods Literature published between January 2010 and April 2024 in 10 electronic databases were searched and screened. This timeframe was established to include studies published within the last 15 years. Each identified article was screened and reviewed by two authors independently. The methodological quality of the included studies was evaluated using the PEDro Scale. Key findings were synthesized according to participants’ characteristics and intervention types. Results The review included 32 studies. In the general community-dwelling older adult population (20 studies), studies that applied functional training as a single-component approach showed a positive effect on activities of daily living. However, the training effect on balance and mobility was not superior to that of other exercise programs. Moreover, the effect was mixed when functional training was combined with other intervention components. In older adults with mild cognitive impairment (5 studies), Simulated Functional Tasks Exercise, a single-component training, consistently demonstrated positive effects on the activities of daily living and cognitive functions. In older adults with dementia (4 studies) or frailty (3 studies), the effect was mixed across the single- and multi-component approaches. Conclusion Functional training alone is effective in preventing late-life disability in general community-dwelling older adults. When training activities challenge both motor and cognitive abilities, the effect seems to improve the performance of activities of daily living and cognitive functions in older adults with mild cognitive impairment. Additional studies of functional training in older adults with cognitive impairment or frailty are recommended.